Pengaruh Technology Acceptance Model (TAM) terhadap Adopsi Kecerdasan Buatan di Kalangan Mahasiswa Akuntansi - Rahmayanti, Dea Putri; Hatta, Madani; Afriazi, Hara (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
Advances in artificial intelligence (AI) technology are rapidly increasing and have affected various sectors, including higher education. In the context of accounting students, the use of AI has the potential to increase learning effectiveness and readiness to face professional demands in the digital age. This study aims to analyze the influence of self-confidence, social norms, management support, perceived usefulness, and perceived ease of use on the adoption of AI by accounting students. The study uses a quantitative approach with an explanatory research method. Data were collected through a questionnaire survey of accounting students at Bengkulu University and analyzed using SmartPLS. The results show that the variables of perceived usefulness and perceived ease of use have a significant influence on AI adoption, while the variables of self-confidence, social norms, and management support contribute indirectly. These findings emphasize the importance of improving technological literacy and institutional support in encouraging the use of AI in educational settings. This study provides theoretical contributions to the development of technology acceptance models and practical implications for universities in designing AI-based learning strategies.